2010
DOI: 10.1095/biolreprod.109.081893
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Infusion of Latency-Associated Peptide (LAP) During Early Porcine Pregnancy Affects Conceptus Elongation and Placental Size1

Abstract: In the pig, transforming growth factor beta (TGFB), TGFB receptors (TGFBRs), and integrins are present during the peri-implantation period. Latency-associated peptide (LAP), a part of latent TGFB, can bind to integrin heterodimers via its Arg-Gly-Asp (RGD) sequence; therefore, ligand-receptor interactions between TGFB and TGFBRs, along with LAP and integrin heterodimers, may be functional in mediating events supporting conceptus elongation and attachment. With the use of surgically implantable osmotic pumps, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…TGFβ1 stimulates human cytotrophoblast cells [40] and porcine trophectoderm cells [14] to produce oncofetal fibronectin, which is important for trophoblast attachment to uterine tissue. TGFβ1 and integrins are involved in conceptus elongation and placental and fetal size [41]. Our present study demonstrated that TGFβ1 may stimulate porcine trophoblast cells proliferation, thus supporting conceptus survival and implantation.…”
Section: Discussionsupporting
confidence: 62%
“…TGFβ1 stimulates human cytotrophoblast cells [40] and porcine trophectoderm cells [14] to produce oncofetal fibronectin, which is important for trophoblast attachment to uterine tissue. TGFβ1 and integrins are involved in conceptus elongation and placental and fetal size [41]. Our present study demonstrated that TGFβ1 may stimulate porcine trophoblast cells proliferation, thus supporting conceptus survival and implantation.…”
Section: Discussionsupporting
confidence: 62%
“…In pigs, TGFB1, TGFB2, and TGFB3, as well as their receptors, TGFBRI and TGFBRII, are expressed by conceptus trophectoderm and by uterine LE between days 10 and 14 of gestation; and acting through LAP, TGFB increases fi bronectin synthesis, cell adhesion to fi bronectin, and the formation of FAs in a porcine trophectoderm cell line (Jaeger et al 2005 ). In addition, when LAP is infused into the uteri of pregnant pigs, conceptuses failed to implant, suggesting that infused LAP competed with the endogenous LLC for binding to integrins expressed on trophectoderm (Massuto et al 2009b ). In support of this idea, aggregates of LAP, β1, β3, and β5, have been detected at the porcine conceptus trophectoderm-uterine LE interface, suggesting functional adhesion complexes that support conceptus attachment during porcine implantation (Massuto et al 2009a ).…”
Section: Trophoblast Attachment and Adhesionmentioning
confidence: 99%
“…Development and attachment of the pig conceptus involves spatiotemporal expression of a similar cascade of paracrine and autocrine cytokines as described for mouse and human implantation. Uterine and/ or conceptus expression of insulin-like growth factors 1 and 2 (IGF1, IGF2; Green et al 1995), IGF-binding proteins (Lee et al 1998; Ashworth et al 2005), epidermal growth factor (EGF; Vaughan et al 1992; Kennedy et al 1994), heparin-binding EGF (Kim et al 1995), transforming growth factors (Massuto et al 2010a, 2010b), leukemia inhibitory factor (LIF; Anegon et al 1994; Modric et al 2000), fibroblast growth factor-7 (Ka et al 2000, 2007), interleukin-1β (IL1B; Tuo et al 1996; Ross et al 2003b), IL6 (Anegon et al 1994; Modric et al 2000), conceptus interferons (IFNτ and IFNΔ; Cross and Roberts 1989; Lefevre and Boulay 1993) and PTGS2 (Wilson et al 2002; Ashworth et al 2006) have been studied during the critical period of conceptus attachment in the pig.…”
Section: Conceptus Signaling and Developmentmentioning
confidence: 99%